Corpus Coranicum and Digital Philology: A Methodological Model for Advancing Qur’anic Manuscript Studies in Indonesia - Syahrullah Syahrullah; Wildan Imaduddin Muhammad; Eva Nugraha; Aulia Raudhatul Jannah (UIN Sunan Gunung Djati Bandung, 2024)
Purpose: This study aims to explore the application of digital philology in Qur’anic manuscript studies, particularly through an analysis of the Corpus Coranicum project as a model for critical engagement with early Qur’anic texts. Methodology: Employing a qualitative approach based on literature review, this research is combined with a case analysis of two core issues: the orthographic variation in early Qur’anic manuscripts and the presence of the ʿUthmānī archetype in written form. Findings: The findings demonstrate that the digital tools within Corpus Coranicum enable more precise and in-depth cross-manuscript textual comparisons. These results reveal orthographic variations based on geographical regions and provide preliminary evidence for the consolidation of the ʿUthmānī text. Research Implications: Implicatively, the study illustrates how digital philology can enrich methodologies in Islamic studies, create opportunities for digital-based academic training, and enhance access to manuscript data. Originality/Value: This research offers an original contribution by emphasizing the importance of integrating digital technologies into Qur’anic studies—particularly in Indonesia, where academic contexts have yet to widely develop this approach.